LOW CD8+ T LYMPHOCYTE/TUMOR BUDDING INDEX PREDICT POSITIVE NODAL STATUS IN BREAST CARCINOMA - Ni Putu Sriwidyani; I Wayan Juli Sumadi (Journal of Global Pharma Technology, 2018)
Introduction: Death in breast cancer patients are mostly caused by the presence of distant metastasis and nodal status is the strongest prognostic factor of metastasis. CD8+ T lymphocyte/tumor budding index is a representation of the anti/protumor properties interaction. The purpose of this study is to prove the interaction between tumor cells and tumor microenvironment and its relationship nodal status in breast carcinoma. Methods: A cross sectional analytic study using 45 cases of breast carcinoma which were underwent mastectomy and radical axillary lymph node dissection at Sanglah Hospital Denpasar during 1 January until 31 December 2017 was conducted. Tumor budding was a small group of cells at the edge of tumor invasion which was evaluated at H-E slide. CD8+ T lymphocyte was evaluated on immunohistochemical slide and was calculated on the peritumoral stroma. Results: Using ROC curve, cut-off value was 4.05. Of all cases, 23 cases with low and 22 cases with high CD8+ T lymphocyte/tumor budding index. CD8+ T lymphocyte/tumor budding index had a significant inverse correlation with nodal status (p=0.000), meanwhile LVI has linier correlation with nodal status in breast carcinoma (p=0.006). Conclusion: there was an inverse relationship between CD8+ T lymphocyte/tumor budding index with nodal status in patients with breast carcinoma